The Effectiveness of Early Interventions in Post-Ischemic Stroke Patients on Neurological Recovery And Quality of Life: A Systematic Review - Wisnu Guntur Prakoso; Sriyono Sriyono; Erna Dwi Wahyuni (Jurnal Ners, 2026)
Abstract Introduction: Individuals recovering from ischemic stroke often endure significant neurological impairments, including motor deficits, cognitive challenges, and emotional disturbances. These complications substantially reduce their quality of life and impose a heavy burden on both the healthcare system and caregivers. Objective: This systematic review aims to evaluate the effectiveness of early interventions in improving neurological recovery and quality of life in post-ischemic stroke patients. Method: A structured literature review was conducted following the PRISMA guidelines. Five major databases (Scopus, PubMed, Science Direct, Web of Science, and ProQuest) were systematically searched using defined keywords. Articles were screened and selected based on pre-established eligibility criteria, and quality appraisal was carried out using Joanna Briggs Institute (JBI) tools. Results: A total of 11 studies met the inclusion criteria. Most early interventions were initiated within 24 to 72 hours after stroke onset. The results consistently showed that early rehabilitation, nursing care, occupational therapy, and other multidisciplinary approaches contributed to significant improvements in neurological function, daily living activities, and health-related quality of life. Conclusion: Early interventions administered during the acute phase of ischemic stroke are effective in enhancing recovery and improving quality of life. These findings highlight the importance of timely, structured, and multidisciplinary stroke rehabilitation programs as a standard part of stroke management. Keywords: Early intervention, ischemic stroke, neurological recovery, quality of life, stroke rehabilitation